Effects of a low-frequency sound wave therapy programme on functional capacity, blood circulation and bone metabolism in frail old men and women - Zheng, A.; Sakari, R.; Cheng, SM; Hietikko, A.; Moilanen, P.; Timonen, J.; Fagerlund, KM; Kärkkäinen, M.; Alèn, M.; Cheng, S. (Clinical rehabilitation, 2009)
Objective: To evaluate the effects of a low-frequency sound wave therapy programme on functional capacity, blood circulation and bone metabolism of the frail elderly. Design: Single-blind, randomized, controlled trial. Setting: Two senior service centres. Subjects: Forty-nine volunteers (14 males and 35 females) aged 62—93 years with up to 12 diagnosed diseases were allocated in either the intervention group (n = 30) or control group (n = 19). Intervention: The intervention group underwent sound wave therapy, 3—5 times a week for 30 minutes per session over a period of 6 months. The control group received no intervention. Main measurements: Blood pressure, functional capacity, mobility, bone density, biochemical markers, isometric muscle strength, balance, and skin surface temperature. Results: Compared with the control group, the intervention group’s mobility and the amount of self-reported kilometres walked per week increased by 3 km (P<0.05), while levels of cholesterol (4.97 (0.72) to 4.52 (0.65) mmol/L, P =0.019), low-density lipoprotein (2.82 (0.72) to 2.45 (0.61) mmol/L, P =0.022), bone markers of total osteocalcin (11.0 (6.5) to 10.3 (5.9) ng/mL, P =0.048)) and tartrate-resistant acid phosphatase isoform 5b (2.50 (1.0) to 2.41 (1.1) IU/L, P =0.021)) decreased. The average skin surface temperature was significantly higher during active sessions at the end of the intervention than in the beginning (P = 0.004). No change was found during placebo sessions. Conclusions: Low-frequency sound wave therapy may have the potential to promote well-being of frail elderly subjects via improved functional capacity, especially in subjects who are too frail to undertake exercise.